Stellar age revealed by chemical composition - Magrini, Laura; Casali, Giada (Il Colle di Galileo, 2021)
High-resolution spectroscopic surveys provide an extraordinary dataset on the processes of the formation and evolution of our galaxy, in which the determination of the ages of individual stars plays a major role. We present here a method for measuring stellar ages based on the carbon/nitrogen abundance ratio in stellar atmospheres. We apply this relationship to the disc of the Milky Way, finding a clear age difference between the thin and thick discs of our galaxy.